Pemanfaatan Instagram Sebagai Media Pemasaran Online PT. Justatrip Sahabat Perjalanan - Yasmin Khalisa Putri; Diana Khuntari (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2023)
The ease of disseminating information about the products offered can influence economic competition in the business sector. Companies must carry out appropriate marketing in order to survive and compete with their competitors. Instagram is one of social media that companies can use to market their products by sharing photos and videos, as PT. Justatrip Sahabat Perjalanan does. This research aims to determine the use of Instagram as an online marketing media for PT. Justatrip Sahabat Perjalanan. The research method used is qualitative using the Marketing Mix theory (7P) by Kotler and Armstrong, namely: product, price, place, promotion, physical evidence, people and process. The data collection techniques used were observation, interviews and documentation. The implementation of the Marketing Mix on the @just_atrip account can be seen through: product and price explanations in the feeds and highlights; direct message as a place to buy and sell products; promotions using the Instagram ads feature, giveaways, direct marketing and public relations via direct message and comments columns; physical evidence in the form of uploads regarding company facilities and characteristics in feeds and highlights; the minimalism and professionalism of people as seen in the reply comments on the feed; as well as a link in the bio of the @just_atrip account as an implementation process that can make it easier for consumers to order travel packages. The research results show that Instagram is used as an online marketing media by applying seven elements of the Marketing Mix so that it can produce positive feedback and increase insight on the Instagram account @just_atrip.